Acute Appendicitis Remains a Great Mimicker – The Pitfalls in the Differential Diagnosis and Tactics - A Case Report - Georgi Popivanov; Marina Konaktchieva; Vladimir Vasilev; Kirien Kjossev; Marin Penkov; Dimitar Penchev (Journal of Biomedical & Clinical Research)
Acute appendicitis (AA) is the most common non-traumatic abdominal emergency. Despite the improved knowledge, experience, and technological advance, its diagnosis remains a challenge. Herein we report an example of a difficult diagnosis of acute appendicitis and comment on the possible pitfalls in the differential diagnosis and surgical tactics. We present the case of a 41-year-old man who had been admitted to another hospital with an initial diagnosis of acute appendicitis and changed to Crohn’s disease (CD). Because of a pelvic abscess, percutaneous drainage had been performed. Thrombosis of the right femoral vein had been diagnosed and treated accordingly. In an improved condition, he was referred for elective operation with a final diagnosis of neuroendocrine tumour based on cytology. At laparotomy, the appendix was found densely adherent to the right external iliac vein with a well-demarcated tumour (1 cm) at the base. Appendectomy with partial resection of the caecum with a linear stapler was performed. The histological examination revealed acute to chronic appendicitis with lymphoid follicle hyperplasia at the base. The case illustrates the necessity for broad differential diagnosis in AA and the possibility of severe vascular complications in complicated AA. Taking a detailed history and CT are of paramount importance for an accurate preoperative diagnosis, especially of CD. All emergency surgeons should also be familiar with the scenario of unexpected findings at laparotomy, especially with the management of CD and the algorithms for treatment of appendiceal malignancies. The mini-invasive drainage of right iliac fossa abscess allows for optimizing the patient’s condition and may help to avoid unnecessary extensive resections.